PERSEPSI DAN PROBLEMATIKA PENGGUNAAN KAMUS DWIBAHASA BAHASA ARAB – INDONESIA TINJAUAN LEKSIKOGRAFI PEDAGOGI - Rustandi, Encep (STIQ Amuntai, 2024)
Bilingual dictionaries are necessary to help learners understand and communicate in the target language, and bilingual dictionaries serve as a second resource when native speakers are not available. The problem is the basis for selecting equivalents and the level of similarity related to the semantic field. This research uses a qualitative descriptive method with library research and quantitative research as support. Researchers used three data collection techniques, namely content analysis, questionnaires and interviews with 173 respondents. Research findings show that aspects of accessibility include the field of morphology: difficulty finding basic words, the semantic field has difficulty finding equivalent words and graphics. About (52.75%), users prefer entries that are appropriate to the context, and (35.16%) prefer entries based on usage examples. The difficulty of using a bilingual Arabic-Indonesian dictionary is caused by language competency factors, both grammar and semantics, design factors including design, dictionary graphics. Then the intensity factor is around (60%) rarely using a dictionary. The results of the survey questionnaire on 91 users showed that (91.21%) felt that they needed training in using dictionaries, this was based on the role of dictionaries, which increased (65.93%) stated that dictionaries had a significant role in study activities. Solution, more than half 58.24% of users chose to switch to electronic dictionaries. So this phenomenon has an impact on users switching to using electronic dictionaries.